Praktičeskaja funkcional'naja grammatika russkogo jazyka - Parmenova, Tat'jana V. (Specimina philologiae Slavicae, 2000)
The importance of the textbook lies in the fact that it is based on a mature theoretical approach, the "Petersburg" functional grammar, which is significantly influenced by the name of A.V. Bondarko is based, which is undoubtedly suitable, with particular attention to the grammatical categories, but also the relevant factual links (i.e., morphological and syntactic categories) to prepare the material for the acquisition of the foreign language Russian onomasiologisch. Such an approach, an essential component of a so-called active grammar, is needed to complement the semasiological approach, which is still often in the foreground.